Presentation Of The Political And Social Scenario In The Short Stories Of Mazhar-Ul-Salam - Rosheen Aqib , Dr. Sadaf Fatima , Dr. Saira Irshad , Dr. Muhammad Rahman , Dr. Mutahir Shah (Migration Letters, 2024)
Mazharul Islam is one of the representative artists of the Indo-Pak. Among the creators who showed their creativity and established their identity on the legendary scene of Urdu in the seventies, the name of Mazharul Islam is among them. It is of considerable importance. Thus, he started writing fiction from 1967, but his creative essence fully emerged in the 1970s and became popular. The era in which he started writing stories was the era of symbols and abstraction and ambiguity were being treated as fashion. They do not fall into the category of abstraction. They gave new meaning to the signs with artistic riad and introduced the modern fictions to the English language. The stories of the early period can be seen in this context. A few stories in “Ghoron kay sheher main akela Aadmi” are[1] definitely symbolic (including “Rait Kinara, “Alif Lam Mim”, “Muthi bhr intizar”, “Ghoron kay sheher main akela Aadmi”, “Azab posh parinday”, “Kandhy par kabouter”, and “Barah Mah” etc. can be added to the list, but it is not that the understanding of these stories is not possible. The specialty of Mazahar ul Islam lies in the fact that he also avoided bold symbols and used symbols that can be understood by discerning readers. In later collections these symbols were discarded altogether and replaced by new symbols. The political and social scenario of his stories is also shown.